1997
DOI: 10.1121/1.418198
|View full text |Cite
|
Sign up to set email alerts
|

On the quasi-analytic treatment of hysteretic nonlinear response in elastic wave propagation

Abstract: Microscopic features and their hysteretic behavior can be used to predict the macroscopic response of materials in dynamic experiments. Preisach modeling of hysteresis provides a refined procedure to obtain the stress-strain relation under arbitrary conditions, depending on the pressure history of the material. For hysteretic materials, the modulus is discontinuous at each stress-strain reversal which leads to difficulties in obtaining an analytic solution to the wave equation. Numerical implementation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(67 citation statements)
references
References 25 publications
4
63
0
Order By: Relevance
“…Any increase in the measured values of these coef®cients re¯ects an increase of the nonlinear hysteresis behaviour of the material. Finally, in agreement with wave propagation experiments, it can be shown that the presence of hysteresis does not affect the level of the even harmonics in resonance [21,32]. As in the case of wave propagation and wave modulation, it is important to note that these results are fundamentally different from a classical approach in which a nonlinear oscillator, such as the Duf®ng type oscillator, is described [37].…”
Section: State Of the Art In Modelling Nonlinearity And Hysteresissupporting
confidence: 62%
“…Any increase in the measured values of these coef®cients re¯ects an increase of the nonlinear hysteresis behaviour of the material. Finally, in agreement with wave propagation experiments, it can be shown that the presence of hysteresis does not affect the level of the even harmonics in resonance [21,32]. As in the case of wave propagation and wave modulation, it is important to note that these results are fundamentally different from a classical approach in which a nonlinear oscillator, such as the Duf®ng type oscillator, is described [37].…”
Section: State Of the Art In Modelling Nonlinearity And Hysteresissupporting
confidence: 62%
“…Strain amplitude effect on wave propagation investigated previously in various studies (Johnson et al 1996, Ten Cate et al 1996, Van Den Abeele et al 1997, Zinszner et al 1997, Tutuncu et al 1994, 1998a, 1998b, Ostrovsky et al 2001. However, such studies are mostly focused on wave attenuation rather than wave velocity.…”
Section: Introductionmentioning
confidence: 85%
“…Since different laminate sequences have different resonant frequency, the frequency shift was normalized to the lowest amplitude resonant frequency f0. Several researchers [20,[36][37][38] The geometric nonlinearity considered in this work can only simulate the classic nonlinear zone as can be seen in Figure 20. The 3 rd strain zone with non-classical nonlinearity exhibiting linear frequency shifts was not observed using the model used in this study.…”
Section: Comparison Between Experiments and Theorymentioning
confidence: 99%
“…from Los Alamos [9][10][11][12][20][21][22][23]. Van Den Abeele, Guyer and McCall [20] used a phenomenological model to show that for a nonlinear hysteretic material, linear softening (i.e.…”
Section: Introductionmentioning
confidence: 99%